Influence of physical-property models on thermal elastohydrodynamic lubrication solutions - Toshiharu KAZAMA (Journal of Advanced Mechanical Design, Systems, and Manufacturing, 2023)
This study numerically obtains the thermal elastohydrodynamic lubrication (TEHL) solutions of different physical-property models of five lubricants and different thermal properties of the solids. The solution was computed at the nominal line contact for both Newtonian and non-Newtonian fluids. The density, viscosity, specific heat, and thermal conductivity were considered functions of temperature and pressure, whereas thermal expansivity was considered a function of pressure. The lubricant models were polyalphaolefin, polyglycol, and three mineral oils with different viscosity grades and the thermal conductivity of the solid materials was set to two different values. The operating parameters were represented by slide-to-roll ratio, load, and speed. The numerical solutions were represented by maximum film temperature and friction coefficient. When the physical and rheological properties of the lubricants were considered individually, the solutions were either over- or underestimated. The thermal conductivity formula model was applicable for calculation. When the physical properties were changed, the non-Newtonian fluids less affected the solutions than the Newtonian fluids, and solids with low thermal conductivity somewhat less affected them than those with high thermal conductivity. The mineral oil with high viscosity grade was sensitive to parameter changes. Overall, the qualitative behaviors of all oil types were almost identical in the lubricant models and solid properties.